2021
DOI: 10.3390/microorganisms9051056
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-Mediated Control of Phytopathogenic Xanthomonads: A Promising Green Solution for the Future

Abstract: Xanthomonads, members of the family Xanthomonadaceae, are economically important plant pathogenic bacteria responsible for infections of over 400 plant species. Bacteriophage-based biopesticides can provide an environmentally friendly, effective solution to control these bacteria. Bacteriophage-based biocontrol has important advantages over chemical pesticides, and treatment with these biopesticides is a minor intervention into the microflora. However, bacteriophages’ agricultural application has limitations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 170 publications
(186 reference statements)
0
24
0
Order By: Relevance
“…In addition to being involved in phage–bacterium interaction, LPS is involved in the interactions between bacteria and plant host as an important surface-associated virulence factor for bacterial pathogens including Xanthomonas [ 44 , 45 , 46 ]. The lack of LPS O-chain led to different host defense responses and reduced virulence in X. campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being involved in phage–bacterium interaction, LPS is involved in the interactions between bacteria and plant host as an important surface-associated virulence factor for bacterial pathogens including Xanthomonas [ 44 , 45 , 46 ]. The lack of LPS O-chain led to different host defense responses and reduced virulence in X. campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…One branch of development for obtaining biocontrol agents is based on bacteriophages and phages, the viruses of bacteria. Apart from their stability in the environment [142], one of the most critical points for the utilisation of biocontrol agents is the definition of their host range. This aspect is critical since the potential dispersal of such agents into the environment should not create problems for beneficial bacterial microflora [143,144].…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Moreover, phages should not interfere with the genetic material of the target plant by r eleasing traits through transduction that could be incorporated into the plant cell [143]. There are many studies demonstrating the in vitro effectiveness of phages and phage cocktails in infecting and killing plant pathogenic bacteria, even though relatively few strains have reached the commercial phase [142][143][144]. This lack of commercial applications could be due to the intrinsic difficulty in establishing a direct correlation between laboratory and field conditions [145].…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Bacteriophages, viruses of bacteria, are considered promising biocontrol agents (Buttimer et al, 2017;Choudhary et al, 2022). Previous studies investigated their potential in use against different genera of phytopathogenic bacteria as previously reviewed (Jones et al, 2007;Buttimer et al, 2017;Stefani et al, 2021). Recently, Rahimi-Midani et al (2018) reported for the first time isolation of phages infecting A. citrulli.…”
Section: Introductionmentioning
confidence: 99%